Individual vs. Combined Short-Term Effects of Soil Pollutants on Colony Founding in a Common Ant Species - Seidenath, Dimitri; Holzinger, Anja; Kemnitz, Klara; Langhof, Nico; Lücker, Darleen; Opel, Thorsten; Otti, Oliver; Feldhaar, Heike (Frontiers in Insect Science, 2021)
Insects are integral to terrestrial life and provide essential ecosystem functions such as pollination and nutrient cycling. Due to massive declines in insect biomass, abundance, or species richness in recent years, the focus has turned to find their causes. Anthropogenic pollution is among the main drivers of insect declines. Research addressing the effects of pollutants concentrates on aquatic insects and pollinators, despite the apparent risk of contaminated soils. Pollutants accumulating in the soil might pose a significant threat because concentrations tend to be high and different pollutants are present simultaneously. Here, we exposed queens of the black garden ant Lasius niger at the colony founding stage to different concentrations and combinations of pollutants (brake dust, soot, microplastic particles and fibers, manure) to determine dose-dependent effects and interactions between stressors. As proxies for colony founding success, we measured queen survival, the development time of the different life stages, the brood weight, and the number of offspring. Over the course of the experiment queen mortality was very low and similar across treatments. Only high manure concentrations affected the colony founding success. Eggs from queens exposed to high manure concentrations took longer to hatch, which resulted in a delayed emergence of workers. Also, fewer pupae and workers were raised by those queens. Brake dust, soot and plastic particles did not visibly affect colony founding success, neither as single nor as multiple stressors. The application of manure, however, affected colony founding in L. niger negatively underlining the issue of excessive manure application to our environment. Even though anthropogenic soil pollutants seem to have little short-term effects on ant colony founding, studies will have to elucidate potential long-term effects as a colony grows.